A Low-Cost Acoustic Emission Sensor Based on Piezoelectric Diaphragm - Viera, Martin A. Aulestia [UNESP]; Gotz, Reinaldo [UNESP]; De Aguiar, Paulo R. [UNESP]; Alexandre, Felipe A. [UNESP]; Fernandez, Breno O. [UNESP]; Junior, Pedro Oliveira [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
Sensor monitoring is widely used in modern industrial automation. Industries require efficient and cost-effective monitoring and control systems. Regarding monitoring, new low-cost piezoelectric sensors have been tested in order to monitor processes through the acoustic activity generated. However, these sensors present the difficulties of being very fragile and being glued directly to the structure, thus being single-use sensors. Thus, the objective of this paper is to present a simple, effective and low-cost approach to increase the robustness of piezoelectric transducers and allow their reuse, such as a commercial acoustic emission sensor. For this, a low-cost piezoelectric diaphragm was encapsulated and tested. The characterization of the sensors is the first step in the analysis of the feasibility of an industrial application. Therefore, the sensor was characterized by the pencil lead break (PLB) method, which is recognized for simplicity and repeatability. A piezoelectric diaphragm and a commercial acoustic emission sensor were used as a comparison. Ten PLB tests were performed on a ceramic surface. Time and frequency analysis demonstrated a clear relationship between the enclosed PZT and the other sensors. Based on the good correlation of the results, it was found that the low-cost enclosed PZT can be used in the monitoring of machining processes, presenting greater robustness and simplicity in practical application.
Keywords: Acoustic emission; digital signal processing; low-cost system; piezoelectric transducer; sensor monitoring